1996
DOI: 10.1136/oem.53.4.241
|View full text |Cite
|
Sign up to set email alerts
|

Chronic respiratory symptoms in children and adults living along streets with high traffic density.

Abstract: Objectives-To investigate if the population living along streets with high traffic density has a higher prevalence of chronic respiratory symptoms. Methods-A sample of 673 adults and 106 children (0-15 years), living along busy traffic streets in the city of Haarlem was compared with a control sample of 812 adults and 185 children living along quiet streets. Exposed and control streets were selected on the basis of model calculations of NO2 concentrations. A postal questionnaire containing questions about resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
146
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(172 citation statements)
references
References 16 publications
22
146
1
3
Order By: Relevance
“…Numerous studies have identified associations between traffic-related air pollution and adverse heath effects either by characterizing exposures to specific pollutants using measurements from a few central ambient sites (Dockery et al 1993;Pope et al 1995;Studnicka et al 1997;Laden et al 2000), or by some measure of traffic (Oosterlee et al 1996;Garshick et al 2003;Heinrich et al 2005;Ryan et al 2005). Yet, by ignoring the contribution of indoor sources and the effect of residential ventilation, it is difficult to accurately estimate personal exposures, especially in an intraurban epidemiological study.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified associations between traffic-related air pollution and adverse heath effects either by characterizing exposures to specific pollutants using measurements from a few central ambient sites (Dockery et al 1993;Pope et al 1995;Studnicka et al 1997;Laden et al 2000), or by some measure of traffic (Oosterlee et al 1996;Garshick et al 2003;Heinrich et al 2005;Ryan et al 2005). Yet, by ignoring the contribution of indoor sources and the effect of residential ventilation, it is difficult to accurately estimate personal exposures, especially in an intraurban epidemiological study.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found an association between traffic volume and the number of hospital admissions for asthma (English et al, 1999), vehicle or truck traffic and self-reported symptoms of asthma (Weiland et al, 1994;Duhme et al, 1996), but others have found no association between asthma and traffic volume (Wilkinson et al, 1999). Truck and road traffic were related to chronic respiratory symptoms and reduced lung function in studies of adolescents (Wjst et al, 1993;Oosterlee et al, 1996;Van Vliet et al, 1997;Brunekreef et al, 1997;Ciccone et al, 1998). Most of these studies used traffic counts as a surrogate for exposure to vehicle emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Other epidemiological studies found an association between automobile [9,10] or truck traffic frequency [11± 13] and wheeze. Higher exposure to truck traffic and black smoke was also associated with impaired forced expiratory volume in one second (FEV1) [14].…”
mentioning
confidence: 97%
“…Not all reports attempted to discriminate between the different phenotypes of these conditions. Reports that provide detailed information suggest an effect on the prevalence of cough and bronchitis, but not on asthma and atopy [2,7,8].Other epidemiological studies found an association between automobile [9,10] or truck traffic frequency [11± 13] and wheeze. Higher exposure to truck traffic and black smoke was also associated with impaired forced expiratory volume in one second (FEV1) [14].…”
mentioning
confidence: 99%